2013
DOI: 10.1002/etep.1863
|View full text |Cite
|
Sign up to set email alerts
|

Optimal multi-objective placement and sizing of passive and active power filters by a fuzzy-improved harmony search algorithm

Abstract: Summary In this paper, the authors present a new method for simultaneous optimal placement and sizing (PLAS) of the passive power filters (PPFs) and active power filters (APFs) with acceptable standard levels. Total harmonic distortion of voltage, total harmonic distortion of current, harmonic transmission line loss and total cost of installed PPFs and APFs are the four objectives considered in the optimization, while individual and total harmonic distortion, fundamental reactive power compensation, parallel a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…The loads, being the source of higher harmonics, are connected to nodes with a voltage of 12.5 kV. This system, with various load configurations, was used in the following works [111,[114][115][116]121,129,131,141,143,147]. The complete list of test systems for individual publications is shown in Table 3.…”
Section: Test Systems and Software Solutionsmentioning
confidence: 99%
“…The loads, being the source of higher harmonics, are connected to nodes with a voltage of 12.5 kV. This system, with various load configurations, was used in the following works [111,[114][115][116]121,129,131,141,143,147]. The complete list of test systems for individual publications is shown in Table 3.…”
Section: Test Systems and Software Solutionsmentioning
confidence: 99%
“…A passive dynamic tunable filter (PDTF), based on the loop control theory, realizes the on-line real-time detection of the dissonance of filter and automatic adjustment of the inductance of electromagnetic coupling reactor, and thus, the frequency of filter is able to couple with harmonic frequency again [24]. After a long-term trial run of the prototype of PDTF, it was observed that the filtering performance of PDTF is closely related to the parameters of main circuit (the parameters of filter capacitor and electromagnetic coupling reactor), and the dynamic filtering performance of PDTF is influenced by the tuning method [25].…”
Section: Performance Test Of Passive Dynamic Tunable Filtermentioning
confidence: 99%
“…To illustrate previous research works which have been conducted regarding the methodology and different types of the filters used in the harmonic compensation framework, Table 1 comprehensively shows the harmonic compensation taxonomy including various studies. [ 7–52 ] Based on the magnitude of the harmonic pollution by NLs, it was decided to utilize one or multiple PPFs and APLCs to participate in harmonic compensation. This framework can consist of an objective function (OF) or multiOFs, uncertainty consideration, single‐objective or multiobjective solution method, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The allocation and sizing of the combination of PPFs and APLCs (hybrid APF) have been applied to the harmonic compensation problem based on different studies. [45][46][47][48][49][50] For instance, due to the nonlinearity and intricacy of the harmonic compensation problem, a combination of optimization methods between melody search and augmented Powell heuristic has been used in the study by Kiani-Moghaddam et al, [45] wherein they comprehensively focused on various uncertainties, such as filter location and harmonic currents generated by NLs. The PSO method has been employed for solving harmonic compensation using the hybrid APF.…”
Section: Introductionmentioning
confidence: 99%